Analysis of the state of electronic banking services in the Arab countries - E. V. Vasilieva; A. Alhannah (Управление)
The analysis of the provision of electronic banking services in Arab countries has been performed. The banking sector is an important part of the economy in any country, however in the Arab countries there are certain problems in the application of the concept of electronic banking. The purpose of this study is a comparative analysis of approaches to the application of information and communication technologies in the banking sector in Algeria, the United Arab Emirates and Syria, identification of the features and bottlenecks in the development of electronic banking services.It has been shown that in order to develop a strong economy and provide quality services that meet customer needs, Arab countries are clearly keen to implement the concept of electronic banking in their banks, but there are still some obstacles which prevent them from competing with international financial organisations. On the other hand, there are several successful scenarios for providing electronic services around the world, for example, the experience of the United Arab Emirates, Algeria, Lebanon and other Arab countries.To assess the level of use of electronic services by the Syrian population at the present time, the authors conducted a survey of clients of the Syrian state and private banks. Based on the survey results, it has been concluded that customers are interested in receiving services in electronic form, but this is hindered by the political situation in the country and a number of other problems. General conclusions have been made about the priority of measures that should be taken at the state level in order for Arab banks to meet modern trends in the financial sector.